2012
DOI: 10.3329/bjvm.v3i2.11404
|View full text |Cite
|
Sign up to set email alerts
|

PRIMARY AND SECONDARY ANTIBODY RESPONSE TO COMPOSITE FORMALIN-INACTIVATED <i>STAPHYLOCOCCUS AUREUS</i>, <i>STREPTOCOCCUS AGALACTIAE</i> AND <i>ESCHERICHIA COLI</i> IN RABBITS

Abstract: Twenty buffaloes clinically positive for mastitis were selected for the collection of milk samples. Staphylococcus aureus, Streptococcus agalactiae and Escherichia coli were isolated from milk of mastitic buffaloes according to the procedures recommended by National Mastitis Council Inc., USA. The composite antigen containing S. aureus, Str. Agalactiae and E. coli was then prepared and the concentration of each isolate was adjusted to 1 x 109 cells / ml. To evaluate the antibody response, nine adult healthy ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
0
0
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
1
0
0
1
Order By: Relevance
“…The present findings also supported the study of Raza et al (2015) who stated that dose-dependent immune response can be elicited up to a definitive bacterial concentration depending upon the type of bacteria and nature of adjuvant used. The results of present study are in agreement with that of Avais et al, (2005) who concluded that the primary IHA antibody response to E. coli of composite Antigen was higher at day-15 compared with S. aureus and S. agalactiae whereas secondary antibody response to S. aureus was higher as compared with Strept. agalactiae and E. coli at day-45.…”
Section: Groupsupporting
confidence: 93%
“…The present findings also supported the study of Raza et al (2015) who stated that dose-dependent immune response can be elicited up to a definitive bacterial concentration depending upon the type of bacteria and nature of adjuvant used. The results of present study are in agreement with that of Avais et al, (2005) who concluded that the primary IHA antibody response to E. coli of composite Antigen was higher at day-15 compared with S. aureus and S. agalactiae whereas secondary antibody response to S. aureus was higher as compared with Strept. agalactiae and E. coli at day-45.…”
Section: Groupsupporting
confidence: 93%
“…Zbog toga se sve više istraţivača opredeljuje za davanje vakcine parenteralno-subkutano u regiju vrata ili subkutano u regiju limfnog čvora, jer je takav način jednostavan za aplikaciju, a izbegnute su i lokalne reakcije tkiva na vakcinu Watson, 1996 (Opdebeeck, 1985;Loeffler, 1987;El Rashidy, 1992;Watson, 1992;Nicerson, 1993;Guidry, 1994;Carter, 2003;Lee, 2005) ili Str. agalactiae (Abubakar, 2006;Avais, 2007;Xu, 2011 Na osnovu ovih ispitivanja odlučeno je da se vakcina aplikuje u dva dela, po 2,5 ml subkutano sa svake strane vrata u brahijalnu regiju.…”
Section: Fiziologija Imunosti Mlečne žLezdeunclassified